2007
DOI: 10.1105/tpc.106.042895
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear-Encoded Factor HCF173 Is Involved in the Initiation of Translation of the psbA mRNA in Arabidopsis thaliana

Abstract: To gain insight into the biogenesis of photosystem II (PSII) and to identify auxiliary factors required for this process, we characterized the mutant hcf173 of Arabidopsis thaliana. The mutant shows a high chlorophyll fluorescence phenotype (hcf) and is severely affected in the accumulation of PSII subunits. In vivo labeling experiments revealed a drastically decreased synthesis of the reaction center protein D1. Polysome association experiments suggest that this is primarily caused by reduced translation init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
112
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 87 publications
12
112
0
Order By: Relevance
“…5), but LPA3 could still assist PSII assembly by interacting with CP43, albeit at reduced efficiency, as manifested by reductions in levels of PSII supercomplexes in the mutants . The tight association of several RNAbinding proteins with the membranes has been implicated in efficient translation of chloroplast proteins (Trebitsh et al, 2001;Ossenbü hl et al, 2002;Schult et al, 2007). In this study, we detected LPA3 in both stroma and membrane thylakoid fractions, suggesting that dynamic partitioning between the stroma and membrane may be an important modulator of the efficiency of PSII assembly.…”
Section: Cooperation Between Lpa2 and Lpa3 Is Essential For Psii Assesupporting
confidence: 49%
See 1 more Smart Citation
“…5), but LPA3 could still assist PSII assembly by interacting with CP43, albeit at reduced efficiency, as manifested by reductions in levels of PSII supercomplexes in the mutants . The tight association of several RNAbinding proteins with the membranes has been implicated in efficient translation of chloroplast proteins (Trebitsh et al, 2001;Ossenbü hl et al, 2002;Schult et al, 2007). In this study, we detected LPA3 in both stroma and membrane thylakoid fractions, suggesting that dynamic partitioning between the stroma and membrane may be an important modulator of the efficiency of PSII assembly.…”
Section: Cooperation Between Lpa2 and Lpa3 Is Essential For Psii Assesupporting
confidence: 49%
“…Reduced PSI levels have also been observed in several other PSII mutants (Meurer et al, 1998;Plü cken et al, 2002;Peng et al, 2006;Ma et al, 2007;Schult et al, 2007). One possibility is that levels of PSI may be light sensitive in the PSII mutants (Plü cken et al, 2002;Schult et al, 2007). Alternatively, the perturbed photosynthetic activities of PSII in the mutant may downregulate the levels of PSI (Bailey et al, 2001;Hager et al, 2002).…”
Section: Reduced Levels Of Psii Protein Contents In Lpa3mentioning
confidence: 95%
“…Whereas some RNA binding proteins are membrane embedded or show reversible association with the membrane (Zerges and Rochaix, 1998;Trebitsh et al, 2001;Ossenbü hl et al, 2002;Zerges et al, 2002;Schult et al, 2007), MCA1 and TCA1, as most trans-acting factors (e.g., CRP1 [Fisk et al, 1999], NAC2 [Boudreau, 2000], MBB1 [Vaistij et al, 2000b], and TAB2 [Dauvillé e et al, 2003]), are found in the chloroplast stroma. The functional significance of these contrasting distributions is still unclear but could reflect differences in the mode of action of nucleus-encoded factors: some may remain bound to polysomes, while others bind transiently to their target mRNA but dissociate once translation is initiated.…”
Section: Discussionmentioning
confidence: 99%
“…The high base-tip ratio of the SODs is also consistent with the proposal that they act as reaction oxygen species (ROS) scavengers in the maintenance of early chloroplast development by protecting the chloroplast nucleoids from ROS . Proteins with a basetip ratio of less than 0.33 (14 proteins) were enriched for proteases (FtsH7/9 and SPPA), DNA repair (both MutS homologs), a few unknown proteins, and a few metabolic enzymes as well as proteins involved with the biogenesis of photosystems (maize homologs of HCF173 [Schult et al, 2007] and LPA1; Fig. 5D; Supplemental Table S5).…”
Section: Developmental Effects On the Core Nucleoid Proteomementioning
confidence: 99%